Elimination of Arctic Variant Rabies in Red Foxes, Metropolitan Toronto - Rosatte, R. C.; Power, M. J.; Donovan, D.; Davies, J. C.; Allan, M.; Bachmann, P.; Stevenson, B.; Wandeler, A.; Muldoon, F.
To control the Arctic variant of rabies virus in red foxes, 332,257 bait doses containing live, attenuated Evelyn-Rokitnicki-Abelseth rabies vaccine were distributed in greater metropolitan Toronto during 1989-1999. Human and pet contact with bait was minimal, and no adverse reactions to the vaccine were noted. Significantly fewer rabid foxes were found during the 17 years after fox baiting (5 cases during 1990-2006) than in the 17 years before (96 cases during 1973-1989). The last report of a rabid fox in metropolitan Toronto was in 1996 (reporting period through September 2006), which confirms that distributing oral rabies vaccine bait is a feasible tactic for the control of rabies in foxes in urban environments.